Effect of the Subsurface Drainage in Improving - Mohamed A.Tert (Mesopotamia Journal of Agriculture)
Applying technicality of the subsurface drainage on the heavy clay soil in Al-Ghab plain expose to seasonal water logging phenomenon. The results showed that the improvement in the each of bulk density, porosity, and the hydraulic conductivity was about 0.12 gram /cm3, 5 % and (0,42 m / day) respectively, and the depth of water table was reduced under field capacity level after 4 months from application as the difference with the control to the depths: 0 – 25 and 25 - 45 and 45 - 65 cm.